Advances in understanding the role of disease-associated proteins in spinal muscular atrophy. (3rd July 2017) - Hosseinibarkooie, Seyyedmohsen; Schneider, Svenja; Wirth, Brunhilde
ABSTRACT: Introduction : Spinal muscular atrophy (SMA) is a neurodegenerative disorder characterized by alpha motor neuron loss in the spinal cord due to reduced survival motor neuron (SMN) protein level. While the genetic basis of SMA is well described, the specific molecular pathway underlying SMA is still not fully understood. Areas covered : This review discusses the recent advancements in understanding the molecular pathways in SMA using different omics approaches and genetic modifiers identified in both vertebrate and invertebrate systems. The findings that are summarized in this article were deduced from original articles and reviews with a particular focus on the latest advancements in the field. Expert commentary : The identification of genetic modifiers such as PLS3 and NCALD in humans or of SMA modulators such as Elavl4 ( HuD), Copa, Uba1, Mapk10 ( Jnk3), Nrxn2 and Tmem41b (Stasimon ) in various SMA animal models improved our knowledge of impaired cellular pathways in SMA. Inspiration from modifier genes and their functions in motor neuron and neuromuscular junctions may open a new avenue for future SMA combinatorial therapies.